THE RELATIONSHIP BETWEEN RAINFALL, AIR TEMPERATURE AND WIND SPEED EFFECTS DENGUE HEMORRHAGIC FEVER CASE IN BENGKULU CITY AT 2009-2014 - Chandra Gunawan Sihombing; Enny Nugraheni; Wahyu Sudarsono (DIPONEGORO MEDICAL JOURNAL (JURNAL KEDOKTERAN DIPONEGORO), 2018)
Background: The disease dengue hemorrhagic fever (DHF) was infectious disease caused by dengue virus (DENV 1,2,3, and 4) which transmitted through the bite of Aedes mosquito. The incident of DHF in the transmission affected by climate factors such as rainfall, air temperature and wind speed which influenced dengue vector. Bengkulu city was area of dengue disease endemic. The research was looking for a relation of dengue cases to climatic variables, which was still not available yet. Therefore, it was necessary to know the relation of climate factors with dengue cases in Bengkulu city for preventation and warning of dengue fever.Methods: This research was analytic observational research by using a design study  ecological according to time. Type of data collected was secondary data. The data derived from Health Departement of  Bengkulu city for dengue cases data in Bengkulu city and BMKG station at Pulau Baii for climate data in Bengkulu city at 2009-2014. The data analyzed by using univariate and bivariate analysis correlation and simple linear regression.Result:The result showed pattern tedency of increasing and decreasing of DHF cases and conditions of climate in Bengkulu city at 2009-2014 were same every year generally. The result of bivariate analysis not showed the strength of the relation of climate variables toward dengue cases. rainfall (r = -0,107; p = 0,372), air temperature (r = 0,041; p = 0,733), wind speed (r = 0,087; p = 0,470).Conclusion: It concluded that there were no correlation between rainfall, air temperature and wind speed toward DHF cases in Bengkulu city at 2009-2014